2020
DOI: 10.1016/j.solener.2020.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cutting parameters on surface integrity of monocrystalline silicon sawn with an endless diamond wire saw

Abstract: The cutting of silicon wafers using multi-diamond wire sawing is a critical stage in solar cell manufacturing due to brittleness of silicon. Improving the cutting process output requires an in-depth understanding of phenomena associated with cutting parameters. In order to investigate the influence of diamond wire sawing on surface integrity of monocrystalline silicon, a looped diamond wire was used and cutting parameters wire cutting speed, feed rate and wire tension were varied. The surface morphology was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…As these processing parameters determine the depth of cut per cutting edge and forces increase with increasing depth of cut [17,29,30], these results were to be expected. The study further confirms increasing roughness with increasing feed speed [3,33] and decreasing cutting speed [3]. The lower significance of grain density on process forces has been observed by Pala et al [17] for cutting silicon.…”
Section: Discussionsupporting
confidence: 79%
“…As these processing parameters determine the depth of cut per cutting edge and forces increase with increasing depth of cut [17,29,30], these results were to be expected. The study further confirms increasing roughness with increasing feed speed [3,33] and decreasing cutting speed [3]. The lower significance of grain density on process forces has been observed by Pala et al [17] for cutting silicon.…”
Section: Discussionsupporting
confidence: 79%
“…Thus, there is a need to understand the mechanical performance of monocrystalline silicon and find out the reasons that limit the quality of wafer cutting. Except for the improvement of diamond-wire cutting itself, mechanical anisotropy [ 5 ] is considered as one of the limitations for the optimization of the cutting parameter [ 6 ], because the properties related to the orientation could affect the mechanical performance while producing the silicon wafers. For example, the growth of monocrystalline silicon is usually along with the <111> orientation family and the wire saw cutting is perpendicular to the <110> orientation family to minimize product loss.…”
Section: Introductionmentioning
confidence: 99%
“…The material removal in brittle mode becomes dominant with higher v f , whereas on increasing v c the ductile mode becomes dominant. Both brittle and ductile cutting modes were observed in the sawn surfaces analyzed and this can be a results of anisotropy of the poly-Si as well as of variations in the protrusion and microgeometry of the diamond grits [13]. Pala et al [26] noted that the diamond grits on the wire surface present different microgeometries and hence the levels of protrusion lie within a range.…”
Section: Morphology Of the Sawn Surfacementioning
confidence: 99%
“…Würzner et al [12] studied the effect of v c on the sawn surface of polycrystalline silicon, which revealed the presence of both tensile and compressive residual stress as well as an inhomogeneous surface roughness when using a high v c . Costa et al [13] showed that silicon sawn by electroplated diamond wire sawing undergoes phase transformation on applying v c ≥ 10 m/s. It was revealed that the intensity and bandwidth of the a-Si phase increases gradually in the v c range from 10 to 20 m/s.…”
Section: Introductionmentioning
confidence: 99%